Performances of short growing photo-insensitive rice varieties to evade cyclonic hazard in the coastal region during Aman season - Isa, Md; Ghosh, Shepon Chandra; Asif, Abdulla Al; Ahsan, SM; Akram, Soleh; Shahriyar, Sayeed; Ali, Akkas (Asian Journal of Medical and Biological Research, 2015)
An experiment was conducted at a farmers field in Bakergonj Upazilla of Barisal district from July 2014 to October 2014 to study the adaptive performance of six aman rice varieties. The varieties included in the study were BRRI dhan62, BINA dhan7, BINA dhan8, BINA dhan10, BINA dhan11, and Maloti (local). The experiment was laid out in a randomized complete block design with three replications. Variety Maloti produced highest plant height (126cm) and BRRI dhan62 produced least plant height (93cm). Variety BINA dhan7 and BINA dhan11 produced highest LAI, total dry matter (g plant-1). Yield of different rice varieties varied significantly. Variety BINA dhan11 gave the highest yield (5.033 t ha-1) which was statistically at par with that of BINA dhan7 (5.00 t ha-1) and BINA dhan8 (4.50 t ha-1), BINA dhan10 (3.933t ha-1), BRRI dhan62 (4.167t ha-1). The highest grain yields of these varieties were obtained to the highest number of bearing tillers m-2. The lowest grain yield (3.50 t ha-1) and straw yield (4.840 t ha-1) were found in Maloti. The shortest period for first flowering (66 days) was observed in BRRI dhan62. Among the varieties, the longest maturity stage (139 days) was observed in local var. Maloti. While the shortest period was observed in BRRI dhan62 (94.5 days). So, the experiment concluded that BINA dhan11 was the highest performing short duration variety followed by BINA dhan7, while BRRI dhan62 and, BINAdhan8, BINAdhan10 performed better among the short duration varieties respectively during aman season to evade cyclonic effect and for cultivating boro rice in Bakergonj Upazilla of Barisal district. Asian J. Med. Biol. Res. June 2015, 1(2): 304-315